2017
DOI: 10.1039/c7nr00908a
|View full text |Cite
|
Sign up to set email alerts
|

Aligned cuboid iron nanoparticles by epitaxial electrodeposition

Abstract: Aligned, individual iron square cuboid nanoparticles have been achieved by taking advantage of epitaxial, three-dimensional-island growth on GaAs(001) during electrodeposition at low deposition rates. The nanoparticles exhibit lateral dimensions between 10 and 80 nm and heights below 40 nm. Surface {100} facets predominate with a thin crystalline oxide shell that protects the nanoparticles during prolonged storage in air. The single crystallinity of the iron in combination with structural alignment leads to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The reason is the magnetocrystalline anisotropy of bcc Fe, which causes the <110> direction to be the magnetically harder axis in bcc iron. Previous discussion 17 revealed that other possible contributions to the in-plane magnetic anisotropy, based on, e.g., shape anisotropy, dipolar interaction between the islands, and/or edge effects are expected to be negligible in comparison to the magnetocrystalline anisotropy. This makes FMR a valuable tool to detect epitaxial alignment, especially for cases like the present one where direct structural investigation by X-ray diffraction is hampered by low material volume and overlapping peaks with the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reason is the magnetocrystalline anisotropy of bcc Fe, which causes the <110> direction to be the magnetically harder axis in bcc iron. Previous discussion 17 revealed that other possible contributions to the in-plane magnetic anisotropy, based on, e.g., shape anisotropy, dipolar interaction between the islands, and/or edge effects are expected to be negligible in comparison to the magnetocrystalline anisotropy. This makes FMR a valuable tool to detect epitaxial alignment, especially for cases like the present one where direct structural investigation by X-ray diffraction is hampered by low material volume and overlapping peaks with the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Epitaxial growth of bcc Fe results in a magnetic anisotropy in the substrate plane that is measurable by comparing the FMR spectra along the <100> and <110> directions. 17 Calculations 21 and experiments 17 show that the resonance spectrum shifts to higher B values when the external B-field is applied along a <110> direction, in comparison to the case where B is applied along a <100> direction. The reason is the magnetocrystalline anisotropy of bcc Fe, which causes the <110> direction to be the magnetically harder axis in bcc iron.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations